Trabalho do/a profissional de Educação Física do NASF na atenção básica à saúde no município de Vitória - ES - Silva, Andre Luis Facanha da (2022)
The main objective of this thesis is to analyze how the Physical Education Professional (PEF - Profissional de Educação Física) of the Family Health Care Center (NASF - Núcleo de Atenção à Saúde da Família) develops his work as well as to understand which learnings and knowledges are required of these professionals to act in health care in the territory. To develop such study participant observations were carried out using the field diary in the work processes of eight PEF of the NASF in their respective health territories in a period of two months. Besides the observations three Expanded Research Groups (GAP - Grupos Ampliados de Pesquisa) were organized which discussed the work processes of Physical Education at NASF. After the first GAP it was carried out simultaneously a participant observation at the Basic Health Units (UBS - Unidades Básicas de Saúde) of the Jardim da Penha, Andorinhas, Santa Marta and Joana D’Arc neighborhoods using the field diary. The data were analyzed in the light of the debate about the health in the area of Physical Education in its interfaces with the field of Collective Health. As a development of the investigation three chapters of analysis were prepared namely: i) physical education and health production: between health technologies and the (mis)matches in primary health care; ii) between understandings and repercussions of the NASF proposal on physical education in ABS/ESF; iii) the common work: the NASF PEF in face of the demand and organization of mental health at ABS. In relation to the NASF PEF the following were identified: the technological production of the PEF`s health work in meetings with users, the teamwork in grouping arrangements and integration with the participation of the PEF and factors that facilitated and restricted the intersectoral performance in the networking. Regarding the NASF as a policy there is a continuity and “more” presence of the Physical Education at ABS even between different forms of organization and the role of the PEF in “being of the NASF”. The proposal of the NASF also made possible the common work of the PEF in the field of mental health at the ABS even being questioned what is the demand of Physical Education, also pointing out assistance, approach and collective work in the organization of mental health at ABS. We conclude that the way of acting of the NASF PEF presents a continuity of health practices already built by the learnings structured by the Physical Education and public health nucleus as well as being among the health practices under construction in which the structuring learnings are found. These in turn are produced in action by the relationships with the health teams facing the health problems and needs of the user of Primary Health Care (Atenção Básica à Saúde) in the city of Vitória-ES.